Kanuka honey versus aciclovir for the topical treatment of herpes simplex labialis: a randomised controlled trial - Nick Shortt; Alex Semprini; Mark Weatherall; Richard Beasley; Irene Braithwaite; Angela Liu; Melanie McConnell; Joseph Singer; Darmiga Thayabaran; Abbie Copinga; Abigail Cadwallader; Ahmad Zareh; et al. (BMJ Open)
Objective To compare New Zealand medical grade kanuka honey with topical aciclovir for the treatment of herpes simplex labialis.Design Prospective parallel randomised controlled open-label superiority trial.Setting 76 community pharmacies across New Zealand between 10 September 2015 and 13 December 2017.Participants 952 adults randomised within the first 72 hours of a herpes simplex labialis episode.Interventions Random assignment 1:1 to either 5% aciclovir cream or medical grade kanuka honey (90%)/glycerine (10%) cream, both applied five times daily.Outcome measures The primary outcome was time from randomisation to return to normal skin (stage 7). Secondary outcomes included time from randomisation to stage 4 (open wound), time from stage 4 to 7, maximal pain, time to pain resolution and treatment acceptability.Results Primary outcome variable: Kaplan-Meier-based estimates (95% CI) for the median time in days for return to normal skin were 8 (8 to 9) days for aciclovir and 9 (8 to 9) for honey; HR (95% CI) 1.06 (0.92 to 1.22), p=0.56. There were no statistically significant differences between treatments for all secondary outcome variables. No related serious adverse events were reported.Conclusion There was no evidence of a difference in efficacy between topical medical grade kanuka honey and 5% aciclovir in the pharmacy-based treatment of herpes simplex labialis.Trial registration number ACTRN12615000648527;Post-results